Storytelling for virtual reality : methods and principles for crafting immersive narratives - Bucher, John K., 1973- (Routledge, Taylor & Francis Group, 2018)
"Storytelling for virtual reality" serves as a bridge between students of new media and professionals working between the emerging world of VR technology and the art form of classical storytelling. Rather than examining purely the technical, the text focuses on the narrative and how stories can best be structured, created, and then told in virtual immersive spaces.